5S method in warehouse management in a municipality of Lima, Peru - Aguirre De la Cruz , Rocío (2024)
Effective warehouse management is crucial in a company's logistics operations but faces challenges, especially in critical delivery stages. Municipal warehouses internationally lack inspection and efficiency due to inadequate policies. According to the World Bank, Peru has deficiencies in warehouse management and productivity. This study aims to enhance a specific warehouse by implementing the 5S, using a pre-experimental design. Results reveal a significant improvement in warehouse management after the 5S implementation at the Municipality, supported by normality tests. It is confirmed that the 5S enhances warehouse management, endorsing the alternative hypothesis.